Difference in outcome between curative intent vs marginal excision as a first treatment in dogs with oral malignant melanoma and the impact of adjuvant CSPG4‐DNA electrovaccination: A retrospective study on 155 cases. (22nd March 2021) - Giacobino, Davide; Camerino, Mariateresa; Riccardo, Federica; Cavallo, Federica; Tarone, Lidia; Martano, Marina; Dentini, Alfredo; Iussich, Selina; Lardone, Elena; Franci, Paolo; Valazza, Alberto; Manassero, Luca; et al.
Abstract: Canine oral malignant melanoma is locally invasive and highly metastatic. At present, the best option for local control is en bloc excision followed by radiation if excision margins are incomplete. Adjuvantly, the role of chemotherapy is dubious while immunotherapy appears encouraging. This retrospective study evaluated 155 dogs with oral malignant melanomas (24 stage I, 54 stage II, 66 stage III and 11 stage IV) managed in a single institution. The aim was to evaluate the differences in median survival time (MST) and disease‐free interval (DFI) between dogs which, at presentation, were treated surgically with a curative intent (group 1) vs those marginally excised only (group 2). MST in group 1 was longer than in group 2 (594 vs 458 days), but no significant difference was found ( P = .57); a statistical difference was, however, found for DFI (232 vs 183 days, P = .008). In the subpopulation of vaccinated dogs, the impact of adjuvant anti‐CSPG4 DNA electrovaccination was then evaluated (curative intent, group 3, vs marginal, group 4); a significant difference for both MST (1333 vs 470 days, respectively, P = .03) and DFI (324 vs 184 days, respectively, P = .008) was found. Progressive disease was significantly more common in dogs undergoing marginal excision than curative intent excision for both the overall population ( P = .03) and the vaccinated dogs ( P = .02). This study pointed out that, after staging, wide excision together with adjuvant immunotherapy was an effective approach for canine oral malignant melanoma.